The Main Challenges Affect Cambodian's Milled Rice Exports - Sinuon Chhun; Mardy Serey (Research of Scientia Naturalis, 2024)
Rice serves as a vital staple for 85% of Cambodian households, particularly those residing in rural areas. The Royal Government of Cambodia (RGC) has prioritized the export of milled rice as a strategic pillar for economic growth, poverty reduction, and improved living standards. However, the export of Cambodian rice faces several challenges, primarily related to meeting the stringent quality standards demanded by high-income markets and increasing competition from producers of fragrant rice. Furthermore, the review identifies obstacles within the governmental processes for rice export documentation, as well as issues impacting rice processing and trading. These challenges include limited government support, financial constraints, unreliable electricity supply, and elevated transportation and milling costs, which ultimately contribute to higher retail prices.